The Authority Of The Local Government Of The City Of Samarinda In Giving License To Open State Land (Study on Samarinda City Regional Regulation Number 2 of 2019 concerning Land Clearing Permits (IMTN) in Samarinda City) - Fachriza Fachriza; Moh. Fadli; Supriyadi Supriyadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This article is entitled "The Authority of the Samarinda City Government in Giving Permits to Open State Land(Study on Samarinda City Regional Regulation Number 2 of 2019 concerning Land Clearing Permits (IMTN) in Samarinda City)" with 2 (two) main issues, namely: (1) Who has the authority to grant permits to open State land according to positive law in Indonesia? (2) How is the existence of the Regional Regulation of the City of Samarinda Number 2 of 2019 concerning Permits to Open State Land (IMTN) in the City of Samarinda. This research is a type of legal research with a normative juridical research method. Besides, this research uses a statutory research approach and a conceptual approach. The results of this article research indicate that substantially the existence of Regional Regulation Number 2 of 2019 concerning Permits to Open State Land violates the concept of authority for the regions. One of them is as referred to in Regional Regulation Number 2 of 2019 concerning Permits to Open State Land where there are 3 parties authorized in issuing permits, namely the Camat, Regional Secretary and Mayor, which violates the provisions in technical regulations, namely Decree of the Head of BPN Number 2 of 2003 concerning Norms and Standard Mechanisms for the Management of Government Authorities in the Land Sector Implemented by District/City Governments that granting permits to clear land is the authority of the Regent/Mayor. As a permit, the government carries out a control function over activities carried out by the community so that they are in accordance with the provisions of the applicable laws and regulations, one of which is clearing land. The conclusion from the author is that the Central Government is the authorized party in granting permits to open state land. This can be seen in the substance of TAP MPR No. IX of 2001 which then issued Presidential Decree No. 34 of 2003 concerning National Policy in the Land Sector, and Decree of the Head of BPN No. 2 of 2003 concerning Norms and Standards of Mechanisms for the Management of Government Authority in the Land Sector Implemented by District/City Government.